UV Curing Effects on Glass Structure and Mechanical Properties of Organosilicate Low-k Thin Films - Gage, D.M.; Guyer, E.P.; Stebbins, J.F.; Zhenjiang Cui; Amir Al-Bayati; Demos, A.; MacWilliams, K.P.; Dauskardt, R.H. (Proceedings of the IEEE International Interconnect Technology Conference, 2006)
Ultra-violet radiation curing has emerged as a promising technique for enhancing the glass structure and mechanical properties of low-k organosilicate thin films. The present work examines the effects of UV curing on the adhesive and cohesive fracture properties of carbon-doped oxide low-k films. Detailed 29 Si and 13 C nuclear magnetic resonance spectroscopy was employed to study the effects of UV curing on glass structure. The UV curing process is demonstrated to improve the glass network by decreasing the number of terminal non-bridging bonds and increasing the number of cross-linking bonds, leading to significant increases in elastic modulus and interfacial fracture energy. However, an interesting finding is that UV curing does not lead to similar improvements in the films' cohesive strength or their resistance to environmentally assisted cracking in chemical environments. Possible mechanisms responsible for this unexpected behavior are discussed